Pengaruh Suhu, Injection Time dan Backpressure Terhadap Cacat Penyusutan Pada Produk Flange - Chandra Dwiaji, YudhI; Muklas, Iwan; Halim, Abdul (Journal of Applied Mechanical Engineering and Renewable Energy, 2024)
Haspel or often called cable reel is the item or tool needed to roll the cable. Usually this cable reel is made of wood. However, over time this haspel has changed, especially in the material used, which is made of plastic or polypropyelene (PP) material. This haspel consists of several components including: Flange and barrel reinforced using steel rods. All these components will be assembled and ready for sale. When assembled, the flange components must require a fairly good precision because the material used is plastic, the shrinkage factor plays a very important role when printed with an injection molding machine. At the time of assembling the plastic haspel, there was a failure when the raft product was too tight and there was also a loose raft, this was due to shrinkage in the flange which caused the barrel component to not fit into the router part of the flange. This makes the assembly work a little longer than usual. In this final project, the author takes steps on how to analyze shrinkage defects in plastic materials, especially for polypropylene materials, starting from the injection molding process and then taking product samples with different levels of testing through parameter settings. Different injection times and backpressures will result in different product sizes and shrinkage values. A good melting temperature value is used for polypropylene material with a flange thickness of 6 mm, and a flange diameter of 850 mm ranging from 210°C - 230°C. Shrinkage defects in polypropylene materials certainly exist, and may be greater than polystyrene materials but can be minimized by setting good process parameters. A good and ideal shrinkage value and according to standards occurs at a temperature setting of 220°C backpressure 0.2 Mpa with an injection time of 20 seconds. With constant parameters, starting from the injection speed of 60 mm/s. Injection pressure 18 Mpa and cooling time 250 seconds.